Design and Implementation of a 3D C-arm Control Service Protocol (RoboLINK) Based on DICOM - Chen GAO; Kun CHENG; Yunheng CHANG; Fei ZHANG; Bing TANG; Sheng HU; Yang CHEN; Yan XI (CT Lilun yu yingyong yanjiu, 2023)
3D imaging technology assisted orthopaedic robot for preoperative planning can improve the accuracy and efficiency of surgery. However, traditional surgical navigation systems based on 3D data currently need pre-operative drawing and manual registration. The surgical steps are cumbersome and new errors may be introduced during manual registration, resulting in the reduction of accuracy. To address this need, in this study, we design a remote device control service protocol (RoboLINK) based on the DICOM protocol, which can be used in operation and provides a novel solution to the current problem. Based on supporting data transmission between two medical devices, motion control instructions can also be transmitted to achieve mutual cooperation between devices. In accordance with this design method, the protocol is tested in a shadow medical 3D C-arm experimental environment and a simulated surgical robot. The results indicate that the RoboLINK protocol can effectively complete the tasks of data transmission and equipment control with the advantages of feasibility and security.